2020
DOI: 10.14336/ad.2020.0428
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Virulence in Aged Patients Might Be Impacted by the Host Cellular MicroRNAs Abundance/Profile

Abstract: The World health organization (WHO) declared Coronavirus disease 2019 (COVID-19) a global pandemic and a severe public health crisis. Drastic measures to combat COVID-19 are warranted due to its contagiousness and higher mortality rates, specifically in the aged patient population. At the current stage, due to the lack of effective treatment strategies for COVID-19 innovative approaches need to be considered. It is well known that host cellular miRNAs can directly target both viral 3'UTR a nd coding region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
150
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(158 citation statements)
references
References 49 publications
1
150
0
Order By: Relevance
“…As one can expect, viruses with high genomic similarity such as SARS-CoV-2/SARS-CoV or HCoV-229E/HCoV-NL63 had higher number of shared binding sites. Similar computational approach to discover direct miRNA-virus interactions was already employed by Fulzele et al (2020) . Namely, using miRDB researchers predicted miRNAs targeting RNAs of SARS-CoV-2 and SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one can expect, viruses with high genomic similarity such as SARS-CoV-2/SARS-CoV or HCoV-229E/HCoV-NL63 had higher number of shared binding sites. Similar computational approach to discover direct miRNA-virus interactions was already employed by Fulzele et al (2020) . Namely, using miRDB researchers predicted miRNAs targeting RNAs of SARS-CoV-2 and SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article, Fulzele et al (2020) found hundreds of miRNAs which can potentially bind to SARS-CoV-2 RNA as well as the RNA of the highly similar SARS-CoV coronavirus. However, this large miRNA list should be narrowed to find high-confidence interactions which should be further experimentally validated.…”
Section: Introductionmentioning
confidence: 99%
“…In silico analysis shows that SARS-CoV-2 may be targeted by over 800 human microRNAs (miRs); circa 65% of which target the related SARS-CoV, but over 300 miRs are unique in comparison. This change in the affected ncRNA network may lead to the different clinical manifestations and infectivity which are apparent in the current pandemic ( 36 ). Since lncRNAs form a complex infection-associated activity profile and may operate as ā€œspongesā€ modulating miR regulatory activities and response to infection ( 37 ā€“ 39 ), we expected changes in the levels of such ncRNAs to relate to the pathogenesis and hyper-inflammatory nature of COVID-19 ( 12 , 40 ) as well as to its predicted risk of neurologic sequelae ( 24 , 41 ā€“ 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, Fulzele with co-authors found hundreds of miRNAs which can potentially bind to the SARS-CoV-2 RNA as well as the RNA of the highly similar SARS-CoV coronavirus (Fulzele et al, 2020). However, this large miRNA list should be narrowed to find high-confidence interactions which should be further experimentally validated.…”
Section: /15mentioning
confidence: 99%